Automated pool detection from satellite images using data mining techniques. (2016) - Kontos, Konstantinos; Maragoudakis, Manolis
A significant part of data mining is image mining, a principle that deals with image data relationship or patterns which are not explicitly found in the images. The basic objective is to gather knowledge from images with some known methods such as image retrieval, image processing and artificial intelligence. Towards this direction, this paper proposes a classification system for identifying pools from satellite area images. For the feature extraction of every photograph, and therefore the creation of the data set, the method of trainable segmentation is applied. In the current approach, genetic algorithms are utilised in an attempt to reduce the feature set to only the informative ones and class imbalance issues were also dealt with by incorporating a hybrid boosting and genetic sub-sampling approach. Results show that the best precision and recall rates are achieved by using a combination of AdaBoost and neural network algorithm.